(untitled) (Pragya Darshan प्रज्ञा दर्शन, 2025)
This article presents findings from a study conducted in Hansapur Village Development Committee (VDC), wards 1, 4, 5, and 6, of Arghakhanchi district, Nepal. The primary objective was to examine the school education of Magar children. Data was collected through interviews with head teachers and school management committee chairpersons, school surveys, and focus group discussions with Magar children and their parents. Analysis of the primary data reveals that poverty, lack of awareness, unemployment, and illiteracy are significant barriers contributing to non-schooling and high dropout rates among Magar children. The study found a lack of specific support mechanisms within community schools to facilitate the continued education of Magar children and integrate them into mainstream education. It recommends that community schools should offer positive incentives like stationery, uniforms, and free admission. Additionally, Parent-Teacher Associations should actively raise awareness about the importance of education within the Magar community